N-terminal pro brain natriuretic peptide eliminates the prognostic effect of atrial fibrillation in patients with chronic heart failure - Schnorbach, Johannes; Fröhlich, Hanna; Täger, Tobias; Corletto, Anna; Katus, Hugo; Frankenstein, Lutz (ESC heart failure, 2019)
Aims Co-morbid atrial fibrillation (AF) increases both mortality and N-terminal pro brain natriuretic peptide (NT-proBNP) concentrations in patients with chronic heart failure (CHF). It is unclear whether AF worsens prognosis independently from NT-proBNP concentrations. If AF was an independent risk factor, NT-proBNP levels for outcome prediction would need to be adjusted in patients with AF. We aimed to analyse the influence of AF on the prognostic value of NT-proBNP in patients with CHF. Methods and results A total of 2541 consecutive CHF patients with sinus rhythm (SR) or AF were identified in the outpatients' CHF registry of the University of Heidelberg, Germany. Of these, 250 patients with SR were individually matched to 250 patients with AF with respect to NT-proBNP, New York Heart Association functional class, sex, age, and aetiology of CHF. In the general sample, both AF and NT-proBNP were associated with all-cause mortality [hazard ratio (HR) = 1.96, 95% confidence interval (CI) 1.61-2.39, P < 0.001; and HR = 1.03 per 1000 ng/L increase, 95% CI 1.02 to 1.04, P < 0.001, respectively]. After matching, NT-proBNP retained its prognostic power (HR = 1.13 per 1000 ng/L increase, 95% CI 1.10 to 1.16, P < 0.001), but AF did not (HR = 0.91, 95% CI 0.66 to 1.25, P = 0.56). Despite similar prognosis, matched patients with SR were in more advanced CHF than were AF patients as indicated by a lower left ventricular ejection fraction (30 ± 13% vs. 34 ± 14%, P < 0.001). Conclusions The prognostic value of NT-proBNP in CHF is not influenced by concomitant AF. AF, in return, might be a surrogate of a worse cardiac condition rather than an independent risk factor.
Published online 1 July 2019
Gesehen am 11.05.2020